2001
DOI: 10.1128/mcb.21.3.952-965.2001
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase SGK Mediates Survival Signals by Phosphorylating the Forkhead Transcription Factor FKHRL1 (FOXO3a)

Abstract: Serum-and glucocorticoid-inducible kinases (SGKs) form a novel family of serine/threonine kinases that are activated in response to a variety of extracellular stimuli. SGKs are related to Akt (also called PKB), a serine/threonine kinase that plays a crucial role in promoting cell survival. Like Akt, SGKs are activated by the phosphoinositide-3 kinase (PI3K) and translocate to the nucleus upon growth factor stimulation. However the physiological substrates and cellular functions of SGKs remained to be identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
681
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 779 publications
(722 citation statements)
references
References 55 publications
26
681
0
8
Order By: Relevance
“…These data suggest that SGK-1 elimination leads to apoptosis, which is supported by previous reports. [26][27][28][29] Next, we confirmed that SGK-1 siRNA could induce apoptosis in another prostate cancer cell line. LNCaP cells were tested using a clonogenic assay.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…These data suggest that SGK-1 elimination leads to apoptosis, which is supported by previous reports. [26][27][28][29] Next, we confirmed that SGK-1 siRNA could induce apoptosis in another prostate cancer cell line. LNCaP cells were tested using a clonogenic assay.…”
Section: Resultsmentioning
confidence: 82%
“…Similar to Akt, SGK-1 has been shown to be a cellular survival factor. [26][27][28][29] Therefore, we examined the role of SGK-1 in AR-dependent survival of prostate cancer cells. First, we tested if eliminating SGK-1 expression induces apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations